The Application of An Audiovisual Flashcard Method to Improve The Applied Understanding of Figured Bass Among Beginner Music Students - Sara Lorin Hernadi; Matthew Hansel; Matius Shan Boone (International Journal Labs, 2026)
This study investigates the effectiveness of an audiovisual flashcard method to enhance beginner music students' applied understanding of figured bass. Figured bass, a core component of Western tonal music theory, is traditionally taught through written analysis, leaving students with limited auditory and practical integration. This gap often results in students recognizing notation visually but struggling to perform harmonically on an instrument. The study aimed to determine whether flashcards could bridge this gap, improve aural skills, and facilitate the practical application of harmonic theory. The research employed a qualitative action research approach involving 25 undergraduate music students at Pelita Harapan University, Class of 2025. Over six learning cycles, students used flashcards containing triads and seventh chords across major and minor scales. Observations, timing of student responses, and questionnaires were collected to evaluate performance and cognitive processing. Results indicate that the flashcard method significantly accelerated students' recognition and execution of figured bass. Students demonstrated improved accuracy, faster response times, and better harmonic internalization. However, some cognitive load challenges emerged with complex chords and inversions. The method also exposed gaps in foundational skills, guiding targeted interventions. In conclusion, audiovisual flashcards effectively transform abstract theoretical understanding into concrete performance skills, enhancing both cognitive and practical learning. Future research should explore digital interactive versions, cross-instrument application, and long-term retention to further optimize multimodal music pedagogy.